Minha trajetória na medicina UFSCAR: uma narrativa reflexiva - Silva, Daniel Souza da (Universidade Federal de São Carlos, 2024)
The medical course at UFSCar adopts active learning as its guiding principle. In active learning, the traditional roles of students and teachers are redefined within a bilateral participatory dynamic, although with a student-centered focus. Students are responsible for actively engaging with problem situations, articulating their conceptions and understandings, and formulating questions that help build bridges between their prior knowledge and the new skills needed to face proposed challenges. The Final Graduation Project (TCC) is a synthesis of the development of the student’s professional practice, constructed from their records and experiences throughout the course. This work aims to present the author’s journey over the six years of the medical program, highlighting the development of competencies, acquired skills, and challenges faced, especially the impact of studying medicine during a global pandemic.
My journey in medicine at UFSCAR: a reflective narrative
Keywords: Medicina; Narrativa reflexiva; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA